Polycarbonate composition as well as preparation method and application thereof
By adding a specific granularized light diffusion agent, chip filler and siliconite to the polycarbonate material, and using polycang acid branches PMMA, the polycarbonate material is solved The problem of insufficient degrees and toughness realizes the high toughness, high luster and high size stability of the material.
Patent Information
- Application Number
- CN202411491544.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-24
- Publication Date
- 2025-01-28
- Estimated Expiration
- 2044-10-24
AI Technical Summary
The existing polycarbonate materials have problems such as deformation, insufficient gloss and toughness in air-conditioning air guide plate parts, especially in the long-term use, the materials are prone to problems such as dimensional instability and reduced gloss.
By adding a specific granularized light diffusion agent, chip filler and siliconite to the polycarbonate material, and using polychikang acid pruning PMMA as the surface modifiers, the support structure is used to improve the toughness and gloss of the material. At the same time, reduce the amount of talc powder.
The high toughness, high luster, and high size stability of polycarbonate materials are realized, and the requirements of the size of the air -conditioning wind guide plate component at high temperature will be less than 1mm at high temperature.
Smart Images

Figure BDA0005100215270000071 
Figure BDA0005100215270000081 
Figure BDA0005100215270000082
Abstract
Description
Technical Field
[0001] The invention belongs to the field of polycarbonate materials, and in particular relates to a polycarbonate composition and a preparation method and application thereof. Background Art
[0002] Polycarbonate (PC) is an engineering plastic with excellent performance. It has comprehensive properties such as high mechanical strength, good impact resistance, dimensional stability, good heat resistance, and good electrical insulation. It is widely used in home appliances, digital products, IT products and other fields.
[0003] Air guide plates for air conditioners are generally made of plastic such as PC, which are long and narrow in shape. They are often deformed due to the effects of gravity and the hot air temperature at the air outlet during long-term use. To overcome this problem, traditional plastic air guide plates need to use aluminum plates as supports to form a composite part with the traditional plastic air guide plates to ensure that the parts do not deform during long-term use. In order to reduce the use of aluminum plates, reduce costs and weight, and achieve one-piece plastic air guide plates with dimensional stability, and to achieve low deformation of plastic air guide plates in long strips, a well-known solution is to increase the rigidity of the material. The traditional solution usually adds some flat or flaky fillers, such as talcum powder, to further increase the modulus of the air guide plate parts, thereby reducing the deformation of the material. However, this solution usually requires the addition of a large proportion of talcum powder (accounting for more than 15% of the mass of PC) to achieve a modulus ≥5200MPa. The addition of a large proportion of talcum powder has limited compatibility with PC. In practice, not only will the toughness of the overall material be reduced, but the uneven surface of flaky materials such as talcum powder will significantly reduce the gloss of the material, and the requirements of the material for high gloss and high toughness cannot be met. Summary of the invention
[0004] In view of the problems of the above-mentioned prior art involving poor structural stability, glossiness and toughness of air-conditioning air guide plate components, the present invention will provide a polycarbonate composition and a preparation method and application thereof.
[0005] To achieve the above purpose, the following technical solutions are specifically included:
[0006] In one aspect, the present invention provides a polycarbonate composition comprising the following components in parts by weight:
[0007] 100 parts of polycarbonate, 0.5-6 parts of flake filler, 7-16 parts of light diffuser, 0.1-3.5 parts of wollastonite, 0.5-6 parts of polyitaconic acid grafted PMMA;
[0008] The light diffuser includes a first light diffuser and a second light diffuser. The first light diffuser has an average particle size of 3-12 μm, the second light diffuser has an average particle size of 50-80 μm, and the second light diffuser accounts for 0-50% of the mass of the light diffuser.
[0009] Wollastonite generally contains needle-like particle morphology and has the characteristics of high aspect ratio, which can greatly improve the modulus of the material, but the presence of wollastonite reduces the toughness and gloss of the material more significantly than the flaky filler. The light diffuser is generally in a microspherical morphology. The inventors of the present invention have found that when a light diffuser, a flaky filler and wollastonite of a specific particle size are present in the polycarbonate composition, a support structure of flaky, needle-like and spherical overlap can be achieved, which can not only reduce the amount of talcum powder, but also effectively reduce the damage to impact and gloss, and ensure the dimensional stability of the material; and the role of itaconic acid grafted PMMA is that PMMA has relatively poor compatibility with PC, and itaconic acid grafted PMMA will preferentially migrate to the surface in the system to make up for the uneven defects formed by the filler to form a mirror surface, thereby effectively improving the gloss, and in the preparation process, the carboxyl group of itaconic acid grafted on PMMA can react with the terminal hydroxyl group of PC to form a chemical bond, which can improve the toughness of the product as a whole, and comprehensively achieve the effects of high toughness, high gloss and high dimensional stability of the polycarbonate composition.
[0010] Preferably, the polycarbonate composition comprises the following components in parts by weight: 100 parts of polycarbonate, 1-5 parts of flake filler, 8-15 parts of light diffuser, 0.2-3 parts of wollastonite, and 1-5 parts of polyitaconic acid grafted PMMA.
[0011] Preferably, in the polycarbonate composition, the mass percentage of the polycarbonate is not less than 50%, more preferably not less than 60%, and even more preferably not less than 75%.
[0012] Preferably, the polycarbonate comprises bisphenol A polycarbonate.
[0013] Preferably, the melt index of the polycarbonate is 6-30 g / 10 min. The melt index of the polycarbonate may be 6, 9, 12, 15, 18, 21, 24, 27, 30 g / 10 min, etc., as well as specific point values between the above point values. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values included in the range.
[0014] Further preferably, the melt index of the polycarbonate is 10-22 g / 10 min.
[0015] The melt index of polycarbonate has a certain influence on the strength of the polycarbonate composition. Within the above-mentioned melt index range, the composition has a more suitable strength and better maintains the good toughness and dimensional stability of the product.
[0016] Preferably, the flaky filler includes at least one of talc powder, mica powder and glass flakes.
[0017] Preferably, the average particle size of the flaky filler is 0.65-11 μm, and the average particle size of the flaky filler can be 0.6, 1, 2, 2.5, 3, 3.5, 4, 4.5, 5, 5.5, 6, 6.5, 7, 7.5, 8, 8.5, 9, 9.5, 10, 10.5, 11 microns, etc., as well as specific point values between the above point values. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values included in the range.
[0018] More preferably, the average particle size of the flake filler is 4.2-5.3 μm. Within the above average particle size range of the flake filler, the polycarbonate composition has better comprehensive performance in terms of flexural modulus, impact strength, glossiness and dimensional stability.
[0019] The D50 of the present invention is measured by laser diffraction.
[0020] Preferably, the light diffuser includes at least one of a silicone light diffuser, a poly(methyl meth)acrylate (PMMA) light diffuser, a polystyrene (PS) light diffuser, and a nylon (PA) light diffuser.
[0021] Further preferably, the light diffuser is a poly(methyl meth)acrylate (PMMA) type light diffuser. Compared with other light diffusers, it has worse compatibility with PC, better maintains a complete microspherical morphology in the system, is more conducive to cooperation with wollastonite and flaky fillers, and is more conducive to improving the gloss of the material. In the present invention, the light diffuser includes a first light diffuser and a second light diffuser. The average particle size of the first light diffuser is 3-12 μm, the average particle size of the second light diffuser is 50-80 μm, the average particle size of the first light diffuser is smaller than that of the second light diffuser, the average particle size of the first light diffuser can be 3, 3.5, 4, 4.5, 5, 5.5, 6, 6.5, 7, 7.5, 8, 9.5, 10, 11.5, 12 microns, etc., the average particle size of the second light diffuser can be 50, 55, 60, 65, 70, 75, 80 microns, etc., as well as specific point values between the above point values. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values included in the said range.
[0022] When the average particle size of the light diffuser is within the above range, the polycarbonate composition has better comprehensive performance in terms of flexural modulus, impact strength, glossiness and dimensional stability.
[0023] Preferably, the mesh number of the wollastonite is 325-1250 mesh. The mesh number of the wollastonite can be 325, 400, 500, 600, 700, 800, 900, 1000, 1100, 1200, 1250, etc., as well as specific point values between the above point values. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values included in the range.
[0024] Further preferably, the mesh size of the wollastonite is 600-800 mesh.
[0025] Preferably, the aspect ratio of the silica is 10-20:1, and the aspect ratio of wollastonite can be 10:1, 11:1, 12:1, 13:1, 14:1, 15:1, 16:1, 17:1, 18:1, 19:1, 20:1, etc., as well as specific point values between the above point values. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values included in the range.
[0026] When the average particle size of wollastonite is within the above range, the comprehensive performance of the polycarbonate composition in terms of flexural modulus, impact strength, glossiness and dimensional stability is better.
[0027] The mesh number of wollastonite is usually measured by conventional methods. The mesh number of wollastonite powder particles is measured by a grid sieving method in the present invention.
[0028] Preferably, the weight percentage of polyitaconic acid in the polyitaconic acid grafted PMMA is 0.5-10%, and more preferably, the weight percentage of polyitaconic acid in the polyitaconic acid grafted PMMA is 1.5-5%.
[0029] Within the above-mentioned grafting ratio range of polyitaconic acid grafted onto PMMA, the polycarbonate composition can have higher glossiness while having higher flexural modulus, impact strength and lower deformation.
[0030] In another aspect, the present invention provides a method for preparing the polycarbonate composition, comprising the following steps:
[0031] The raw materials are sequentially mixed, melted, extruded, cooled and dried to obtain the polycarbonate composition.
[0032] Preferably, the melting temperature is 250-280°C.
[0033] Preferably, the rotation speed during melting is 400-600 rpm.
[0034] Preferably, the melting is carried out under vacuum conditions, and the vacuum degree is -0.07 to 0.08 MPa.
[0035] The present invention also provides an application of the polycarbonate composition in the preparation of an air guide plate component for an air conditioner, wherein the polycarbonate composition satisfies the following requirements: glossiness at an angle of 60 degrees ≥ 102, bending modulus ≥ 5200 MPa, notched impact strength ≥ 50 kJ / m 2 After being made into an air-conditioning air guide plate, the dimensional deformation is less than 1 mm after being hot-baked at 70°C for 168 hours. Therefore, the polycarbonate composition of the present invention has excellent toughness, dimensional stability and high gloss, and is suitable for the new needs of the air-conditioning air guide plate industry.
[0036] Compared with the prior art, the present invention has the following beneficial effects: the polycarbonate composition of the present invention contains a light diffuser, flaky filler, wollastonite and polyitaconic acid grafted PMMA of a specific particle size, so that the polycarbonate composition has excellent toughness, dimensional stability and high gloss, and is suitable for the new needs of the air guide plate industry of air conditioners. DETAILED DESCRIPTION
[0037] In order to better illustrate the purpose, technical scheme and advantages of the present invention, the present invention will be further described below through specific examples. The test methods used in the examples and / or comparative examples are conventional methods unless otherwise specified; the materials, reagents, etc. used can be obtained from commercial channels unless otherwise specified. The components and raw materials used in the examples and comparative examples of the present invention are the same unless otherwise specified.
[0038] The raw material information involved in the following examples and comparative examples:
[0039] Polycarbonate 1: PC WY-106BR, melt index 6g / 10min, Lihuayi;
[0040] Polycarbonate 2: PC 2100, melt index 10g / 10min, Wanhua Chemical;
[0041] Polycarbonate 3: PC 2220, melt index 22g / 10min, Wanhua Chemical;
[0042] Polycarbonate 4: PC H-3000F, melt index 30g / 10min, Mitsubishi, Japan;
[0043] Talc 1: TYT-8005, D50 5.3 μm, Guangzhou Tianyuan Chemical Co., Ltd.;
[0044] Talc 2: TY90-20-A, D50 8.5 μm, Dongguan Sanzhi New Materials Co., Ltd.
[0045] Talc 3: HTP Ultra5L, D50 0.65 μm, Liaoning Aihai Yimi Mining Co., Ltd.;
[0046] Talc 4: TYT-3000A, D50 4.2 μm, Guangzhou Tianyuan Chemical Co., Ltd.
[0047] Mica powder: ym-012, D50 10 microns, Malin;
[0048] First light diffusing agent (small particle size):
[0049] Light diffuser 1: JX-N3, polymethyl methacrylate microspheres, D50 3 μm, Shenzhen Juxin Plastics Import & Export Co., Ltd.
[0050] Light diffuser 2: JX-7G, polymethyl methacrylate microspheres, D50 7 μm, Shenzhen Juxin Plastics Import & Export Co., Ltd.;
[0051] Light diffuser 3: JX-S12, polymethyl methacrylate microspheres, D50 12 μm, Shenzhen Juxin Plastics Import & Export Co., Ltd.
[0052] Light diffuser 4: JX-N20, polymethyl methacrylate microspheres, D50 20 μm, Shenzhen Juxin Plastics Import & Export Co., Ltd.
[0053] Second light diffuser (large particle size):
[0054] Light diffuser 5: JX-G50, polymethyl methacrylate microspheres, D50 50 μm, Shenzhen Juxin Plastics Import & Export Co., Ltd.
[0055] Light diffuser 6: JX-P75, polymethyl methacrylate microspheres, D50 75 μm, Shenzhen Juxin Plastics Import & Export Co., Ltd.
[0056] Light diffuser 7: JX-80R, polymethyl methacrylate microspheres, D50 80 μm, Shenzhen Juxin Plastics Import & Export Co., Ltd.
[0057] Light diffuser 8: JX-100, polymethyl methacrylate microspheres, D50 100 μm, Shenzhen Juxin Plastics Import & Export Co., Ltd.
[0058] Wollastonite 1: LY-0026 1250 mesh, Jiangxi Liyuan Powder Technology Co., Ltd., aspect ratio 10-20:1;
[0059] Wollastonite 2: LY-0023 800 mesh, Jiangxi Liyuan Powder Technology Co., Ltd., aspect ratio 10-20:1;
[0060] Wollastonite 3: LY-0020 400 mesh, Jiangxi Liyuan Powder Technology Co., Ltd., aspect ratio 20-30:1;
[0061] Wollastonite 4: WFC5-2101 325 mesh, Hubei Fengjiashan Silica Fiber Co., Ltd., aspect ratio 11:1.
[0062] The raw materials of itaconic acid grafted PMMA are all homemade, and the homemade method is as follows:
[0063] PMMA (polymethyl methacrylate, purchased from Sinopec Baling Petrochemical Co., Ltd.) with a weight of M1 is dissolved in carbon tetrachloride to prepare a solution with a PMMA mass concentration of 2%; the solution is heated to 60°C, and an ethanol solution of itaconic acid containing a weight of M2 and an ethanol solution of ammonium persulfate containing a weight of 0.5×M2 are added dropwise. After reacting for 4 hours, the solution is first washed with ethanol to remove PMMA insoluble in ethanol, and then a 10% sodium hydroxide solution is used to precipitate the polyitaconic acid grafted PMMA obtained by the reaction, and then washed three times with water to obtain a solid product polyitaconic acid grafted PMMA with a weight of M3. The grafting rate of polyitaconic acid grafted PMMA = (M3-M1) / M1*100%. Different grafting rates can be achieved by adjusting the amount of itaconic acid added.
[0064] Based on the above homemade preparation method, the following four surface modifiers can be prepared:
[0065] Surface modifier 1: polyitaconic acid grafted PMMA, the weight content of polyitaconic acid is 0.5wt%;
[0066] Surface modifier 2: polyitaconic acid grafted PMMA, the weight content of polyitaconic acid is 1.5wt%;
[0067] Surface modifier 3: polyitaconic acid grafted PMMA, the weight content of polyitaconic acid is 5.0wt%;
[0068] Surface modifier 4: polyitaconic acid grafted onto PMMA, the weight content of polyitaconic acid is 10 wt%.
[0069] Examples 1-23 and Comparative Examples 1-8
[0070] A method for preparing a polycarbonate composition comprises the following steps:
[0071] (1) According to the dosage of the raw material components in Table 1-2, the components were mixed in a high-speed mixer for 10 minutes to obtain a premix;
[0072] (2) The premix is fed into a twin-screw extruder through a feeder, the screw speed is 500 rpm, the processing temperature is 260° C., double vacuum is used, and the vacuum degree is -0.07 MPa. The polycarbonate composition is obtained by melt dispersion, blending, extrusion, drawing, cooling, drying, and pelletizing.
[0073] Performance Test:
[0074] (1) Flexural modulus: The polycarbonate composition particles of the above-mentioned examples and comparative examples were dried in an oven at 120° C. for 4-6 h, and then injection molded into ISO 178-2010 standard specimens on an injection molding machine at 300° C., and subjected to a bending test at a rate of 2 mm / min in accordance with the standard, and the flexural modulus was recorded.
[0075] (3) Notched impact strength: The polycarbonate composition particles of the above-mentioned embodiments and comparative examples were dried in an oven at 120° C. for 4-6 h, and then injection molded into ISO 180-2023 standard specimens on an injection molding machine at 300° C. The notched impact strength of the cantilever beam was tested in accordance with the standard, and the notched impact strength was recorded.
[0076] (4) 60-degree angle gloss: The polycarbonate composition particles of the above-mentioned examples and comparative examples were dried in an oven at 120°C for 4-6 hours. They were injection molded into 100*100*2.0 mm square plates at 300°C on an injection molding machine. The square plates were tested using a gloss meter, and the 60-degree angle gloss data were selected and recorded.
[0077] (5) Deformation test during hot baking: The polycarbonate composition particles of the above-mentioned embodiments and comparative examples were baked in an oven at 120°C for 4 hours, and then injection molded into air guide plate parts at 290°C. The molded parts were placed at room temperature for 24 hours for qualitative analysis, and then placed in an oven at 70°C. The air guide plate was fixed with two brackets with a fixed distance of 60 cm. After baking for 168 hours, the parts were taken out and cooled to room temperature. The deformation of the middle part of the air guide plate was tested, which was required to be no greater than 1 mm.
[0078] Table 1
[0079]
[0080]
[0081] Table 2
[0082]
[0083]
[0084] It can be seen from the above examples that the polycarbonate composition of the present invention has a glossiness of ≥102 at a 60 degree angle, a flexural modulus of ≥5200 MPa, and a notched impact strength of ≥50 kJ / m 2 When the air guide plate made into an air conditioner is baked at 70° C. for 168 hours and the dimensional deformation is less than 1 mm, and the above performance requirements are met, the polycarbonate composition is qualified and can meet the requirements of practical applications.
[0085] (1) As can be seen from Examples 1-4, the variable is the melt flow rate of PC. As the melt flow rate of PC increases, the flexural modulus of the polycarbonate composition increases, the notched impact decreases, the gloss increases, and the deformation gradually decreases to a small change. Therefore, the present invention selects a PC melt flow rate of 6-36 g / 10 min, and more preferably 10-22 g / 10 min, at which the PC melt flow rate can maintain good toughness and dimensional stability.
[0086] (2) It can be seen from Examples 2, 5-7 that the average particle size of the talc powder in Examples 6, 7, 2, and 5 gradually increases, the flexural modulus gradually increases, and the notched impact, gloss, and deformation gradually decrease. When the average particle size is 0.65-8.5 μm, the polycarbonate composition is qualified in terms of flexural modulus, impact strength, gloss, and deformation.
[0087] (3) It can be seen from Examples 2, 9-11 and Comparative Examples 4-5 that, in the polycarbonate composition, although both the first light diffuser and the second light diffuser can make the impact strength and deformation amount qualified, the first light diffuser can be used alone in the system of the present invention, but the second light diffuser cannot be used alone. When the first light diffuser and the second light diffuser are compounded, the bending modulus and glossiness are better, and the mass of the second light diffuser should be less than 50% of the total mass of the light diffuser to make the glossiness qualified. And it can be seen from Examples 2, 12-14 and Comparative Example 3 that when the first diffuser and the second diffuser are compounded, the average particle size of the first diffuser or the second diffuser will affect the compounding effect of the two and whether the glossiness is qualified. Therefore, the average particle sizes of the first diffuser and the second diffuser need to be 3-12μm and 50-80μm respectively.
[0088] (4) It can be seen from Examples 2 and 16-18 that the average particle size of wollastonite in Examples 16, 2, 17, and 18 gradually decreases, the flexural modulus gradually increases, and the impact strength, glossiness, and deformation all gradually decrease. The average particle size of wollastonite can be selected to be 325-1250 mesh, and more preferably 600-800 mesh, when the comprehensive performance of the polycarbonate composition is better.
[0089] (5) Comparative Example 1 uses only talcum powder without wollastonite, and its bending modulus, glossiness and deformation are all unqualified; Comparative Example 8 uses only wollastonite without talcum powder, and its glossiness and deformation are all unqualified; Comparative Example 6 does not add a light diffuser, and its glossiness and deformation are all unqualified, and it is impossible to achieve a supporting structure of overlapping needle-shaped wollastonite and spherical light diffusers, resulting in the material's bending modulus, dimensional stability and glossiness failing to meet the requirements; Comparative Example 7 lacks a surface modifier, and its impact strength and glossiness are all unqualified. It can be seen that only when wollastonite, talcum powder, a light diffuser and a surface modifier are present at the same time can the material maintain better toughness and glossiness at the same time.
[0090] (9) It can be seen from Examples 2 and 19-21 that the grafting rate of the surface modifiers of Examples 19, 20, 2, and 21 gradually increases, the surface bending modulus slightly decreases, the impact strength gradually increases, the gloss gradually decreases, and the deformation gradually increases. Itaconic acid grafted PMMA increases the compatibility and toughness of the system. On the one hand, as the grafting rate increases, the compatibility of PC and itaconic acid grafted PMMA becomes better, and its content migrating to the surface of the material decreases, and the degree of compensating for the uneven defects formed by the filler to form a mirror surface is reduced. Therefore, the gloss of the material will be reduced to a certain extent; increased compatibility will also lead to a decrease in modulus and an increase in toughness. The higher the modulus, the stronger the ability to resist deformation, so the modulus decreases and the deformation increases.
[0091] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit the scope of protection of the present invention. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solution of the present invention can be modified or replaced by equivalents without departing from the essence and scope of the technical solution of the present invention.
Claims
1. A polycarbonate composition, characterized in that The composition comprises the following components in parts by weight: 100 parts of polycarbonate, 0.5-6 parts of flake filler, 7-16 parts of light diffuser, 0.1-3.5 parts of wollastonite, 0.5-6 parts of polyitaconic acid grafted PMMA; The light diffuser includes a first light diffuser and a second light diffuser. The first light diffuser has an average particle size of 3-12 μm, the second light diffuser has an average particle size of 50-80 μm, and the second light diffuser accounts for 0-50% of the mass of the light diffuser.
2. The polycarbonate composition according to claim 1, wherein The polycarbonate has a melt index of 6-30 g / 10 min, wherein the melt index is tested according to ISO 1133-1 2011 standard under the test conditions of 300° C. and 1.2 kg.
3. The polycarbonate composition according to claim 1, wherein The flake filler includes at least one of talc powder, mica powder and glass flakes.
4. The polycarbonate composition according to claim 1, wherein The average particle size of the flake filler is 0.65-11 μm.
5. The polycarbonate composition according to claim 1, wherein The light diffuser includes at least one of a silicone light diffuser, a poly(methyl)acrylate light diffuser, a polystyrene light diffuser, and a nylon light diffuser.
6. The polycarbonate composition according to claim 1, wherein The mesh number of the wollastonite is 325-1250 meshes.
7. The polycarbonate composition according to claim 1, wherein The weight percentage of polyitaconic acid in the polyitaconic acid grafted PMMA is 0.5-10%.
8. A method for preparing the polycarbonate composition according to any one of claims 1 to 7, characterized in that: The method comprises the following steps: mixing, melting, extruding, cooling and drying various raw materials to obtain the polycarbonate composition.
9. Use of the polycarbonate composition according to any one of claims 1 to 7 in preparing an air guide plate component for an air conditioner.
Citation Information
Patent Citations
Flame retardant PC / ABS composite with high rigidity and high stability
CN101787194A
Polycarbonate composition and preparation method thereof
CN114591614A
Polycarbonate material as well as preparation method and application thereof
CN114644821A
Polycarbonate material with high paper feeding smoothness as well as preparation method and application of polycarbonate material
CN115403914A
Polycarbonate composition as well as preparation method and application thereof
CN117844218A